Corticosteroid regulation of colonic ion transport during postnatal development: methods for corticosteroid analysis - Pácha, J; Miksík, I; Mrnka, L; Zemanová, Z; Bryndová, J; Mazancová, K; Kucka, M (Physiological research, 2004)
Many mammalian species including human are immature at birth and undergo major developmental changes during suckling and weaning period. This problem is also conspicuous for the gastrointestinal tract that undergoes abrupt transitions coinciding with birth and weaning. This review deals with the maturation of ion transport functions in colon, the intestinal segment that plays an important role in sodium and potassium absorption and secretion. The purpose of the present review is to summarize the mechanism of sodium and potassium transport pathways and show how these transport processes change postnatally and how hormones, particularly corticosteroids, modify the pattern of development. Finally we describe some of the ways, how to analyze corticosteroid metabolism in target tissue.
Keywords: hormony kůry nadledvin; iontový transport; Chromatography, High Pressure Liquid; Glucocorticoids; Adrenal Cortex Hormones; kolon; sodíko-draslíková ATPasa; Electrophoresis, Capillary; Animals; lidé; elektroforéza kapilární; glukokortikoidy; Ion Transport; Sodium-Potassium-Exchanging ATPase; Humans; zvířata; Colon; vysokoúčinná kapalinová chromatografie